POTENSI ENHYDRA FLUCTUANS LOUR SEBAGAI BAHAN BAKU RAMAH LINGKUNGAN DALAM EKONOMI HIJAU - Rahman, Defri; Fachri, Ahmad; NST, Nur Aisyah; Ramadhi (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The aim of this research is to determine the use of cikarau leaves (Enhydra Fluctuans Lour) in society and to calculate the potential for processing cikarau leaves into environmentally friendly raw materials within the framework of a green economy. The research method used is descriptive quantitative. For the first objective, data was collected from 150 respondents using a questionnaire and Likert scale to understand the use of cikarau leaves (Enhydra Fluctuans Lour) in the community. Meanwhile, for the second objective, the potential of cikarau leaves (Enhydra Fluctuans Lour) as an environmentally friendly raw material in the green economy is calculated through analysis of the added value of cikarau leaves (Enhydra Fluctuans Lour) which are processed into cikarau leaf tea. The research results showed that the majority of respondents did not know about the cikarau plant (Enhydra Fluctuans Lour), with only a small portion having more advanced knowledge about it. In terms of experience, direct encounters with plants are also very limited. In terms of utilization, confidence in the medicinal benefits of cikarau leaves (Enhydra Fluctuans Lour) for diseases such as diabetes mellitus and cancer is relatively low. Regarding cultivation, the low level of participation in the cultivation of cikarau plants (Enhydra Fluctuans Lour) shows that this plant is not yet popular for cultivation. From an economic perspective, the margin allocated to company profits is higher than revenue. This indicates that processing cikarau leaves into cikarau tea has promising prospects.